DOI: 10.25148/etd.fi10120803
|View full text |Cite
|
Sign up to set email alerts
|

Parental Absence and Academic Achievement in Immigrant Students

Abstract: and has proven herself to be an expert in the field. Dr. Montgomery's professionalism is something to be admired. Dr. Dionne Stephens has proven to be one of the most inspirational people I have encountered at FIU. Not only did she provide helpful insight regarding the dissertation project along the way, but she also provided much needed support throughout the process. I have come to truly care for Dr. Stephens and not only consider her to be a role model but also a dear friend.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 94 publications
0
2
0
Order By: Relevance
“…Studies on the change of school is usually mention the support of the old peer Bellmore, 2011;Langenkamp, 2010), teacher support (Espinoza, Wang, Juvonen, 2011; Bellmore, 2011), parental involvement in education (Wright, 2010). Other authors Mortlock, Plowman, Glasgow (2011) argues that the success of a child's school change depends on relationships with others, and a comprehensive help:…”
Section: Introduction and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on the change of school is usually mention the support of the old peer Bellmore, 2011;Langenkamp, 2010), teacher support (Espinoza, Wang, Juvonen, 2011; Bellmore, 2011), parental involvement in education (Wright, 2010). Other authors Mortlock, Plowman, Glasgow (2011) argues that the success of a child's school change depends on relationships with others, and a comprehensive help:…”
Section: Introduction and Methodologymentioning
confidence: 99%
“…And in most cases, it occurs because of the serious adaptation period, the transition from the old school to the new homeland of foreign schools (Yuen, 2007;Rice, Frederickson, Seymour, 2011). However, research has shown that those children who were provided with assistance are dealing better with difficulties of school exchange (Silver, Measelle, Armstrong, Essex, 2010;Wright, 2010;Tan, Goldberg, 2009;Cowan, Cowan, 2009;Rupšienė et al, 2005). These results confirmed that the school change is a complex social pedagogical phenomenon with a significant influence on a child's development and evolution.…”
Section: Introduction and Methodologymentioning
confidence: 99%